Digital information resources preferences and evaluation criteria used by the final year engineering undergraduates: A Case Study - Wijetunge, Pradeepa; Peiris, Neetha Damayanthi (My University, 2017)
The purpose of this paper is to present one aspect of the findings of a major study carried out to assess the information seeking and research strategies of the undergraduates of University of Peradeniya, Sri Lanka and the paper serves four objectives; 1) to explore the student‟s preferences of information resources, 2) to identify the criteria they use to evaluate the digital information sources, 3) to recognize the strengths and weaknesses of their information seeking practices and 4) to make appropriate recommendations to strengthen their information seeking practices. A stratified random sample of second, third and fourth year undergraduates were considered for the main survey and accordingly 10% (40 students) of the final year students of the Faculty of Engineering were considered for this paper. Head and Eisenberg‟s (2009) survey instrument was used to gather data. Findings established that the final year engineering students rely more on search engines, Wikipedia and classmates while scholarly databases are used only by a smaller percentage. It was established that the engineering students have higher preference for some digital resources than the other types of resources. In using evaluation criteria they predominantly use self-taught methods instead of traditional reliable methods. It could be inferred that they encounter problems in selecting the most appropriate digital information resources for their academic research. The study further established that majority of the engineering students have not received any formal training in searching or evaluating of digital resources. They have commented that it would be beneficial to have training in the use of library and internet resources. The present study fills the gap in research about the information seeking behavior of engineering undergraduates of University of Peradeniya and it will contribute to the global body of literature in this aspect. It is also expected that the findings will underpin the development of future information literacy programs to be offered through the library.
Keywords: Sri Lanka, Undergraduates, Engineering students, Information seeking behavior, Digital information resources, Evaluation of information resources